Integrasi Perkembangan Moral Dengan Perilaku Sosial Dalam Perspektif Islam Dan Barat - Syafnidawati Syafnidawati (Oasis : Jurnal Ilmiah Kajian Islam, 2024)
This study aims to find and determine the integration between moral development and social behavior when examined from an Islamic and western perspective which includes the perspective of the Qur'an, Hadith, Islamic scientists and western scientists. This research is motivated by many studies that discuss moral development in the view of western scientists and Islamic scientists. This is the driving factor for conducting this research. This research was conducted with a qualitative approach with a literature study method. The data is searched by searching through various literatures ranging from the Qur'an, Hadith and various references related to moral development and social behavior. The search result data is analyzed and presented in a narrative manner. The results showed that there was an integration between moral development and social behavior. Moral development greatly influences social behavior. Good social behavior is formed from good moral development and bad social behavior arises from bad moral development as well